Association Between Blood Pressure Variability and Short-Term Outcome After Intra-arterial Thrombectomy in Acute Stroke Patients With Large-Vessel Occlusion - Yang, Mengqi; Lu, Tao; Weng, Baohui; He, Yi; Yang, Hong (Frontiers in Neurology, 2021)
Background and Purpose: The optimal range of blood pressure variability (BPV) for acute stroke patients with large-vessel occlusion (LVO) remains unclear. This study aimed to evaluate the association between BPV from admission to the first 24 hours after intra-arterial thrombectomy (IAT) and short-term outcomes in LVO patients. Methods: We retrospectively analyzed 257 consecutive patients with LVO stroke who treatment with IAT. Blood pressure (BP) values were recorded at an interval of 2-hour from admission to the first 24 hours after IAT. BPV was reflected by pulse pressure variability (PPV) and was determined as standard deviation (SD), coefficient of variation (CV), successive variation (SV) , and the difference between maximum and minimum (ΔBP) for pulse pressure (systolic BP minus diastolic BP). The association between BPV and the clinical outcome (modifed Rankin Scale [mRS] at 90 days) was analyzed by multivariable logistic regression analysis. Results: Among the 257 included patients, 70 patients had good outcome at 3 months. The PPV from admission to the first 24 hours after IAT were independently associated with the poor outcome in a graded fashion (multivariable-adjusted odds ratios [95% confdence interval] in the highest of PPV was 43.0 [8.7–212.8] for SD, 40.3 [9.8–165.0] for CV, 55.0 [11.2–271.2] for SV, 40.1 [8.0–201.9] for ΔBP). The area under the curve (95% confidence interval) of the PPV parameters respectively were 0.924 (0.882-0.965) for SD, 0.886 (0.835-0.938) for CV, 0.932 (0.891-0.973) for SV, 0.892 (0.845-0.939) for ΔBP, and the Youden Index were 0.740, 0.633, 0.759, and 0.756, respectively. Conclusions: BPV from admission to the first 24 hours after IAT was independently associated with poor outcome at 3 months of patients with LVO, the greater the variability the stronger the association. PPV may be a novel predictor of functional prognosis in LVO patients with IAT.